Ethno-culture varieties of management culture and socio-normative prerequisites of its development - YASHNYK, Svitlana (Journal of Education, Technology and Computer Science, 2014)
The paper justifies socio-normative prerequisites for the formation of labour behavior and management culture, highlights the cultural and ethnic variability of management culture; notes that ethnic mentality, social values, economic activity, industrial relations and the system of according to ethnicity, sets specific direction of the management culture.